12 rules for life an antidote to chaos - Peterson, Jordan B. (London Allen Lane, 2012)
Humorous, surprising and informative, Dr. Peterson tells us why skateboarding boys and girls must be left alone, what terrible fate awaits those who criticize too easily, and why you should always pet a cat when you meet one on the street.
Includes bibliographical references (pages 371-389) and index.
Keywords: Conduct of life--Philosophy.